Towards a change in the fashion and luxury sector. From the domain of the influencer to the brand: Gucci, Loewe and Margiela - Sanz Marcos, Paloma (2020)
The influencer, considered a key asset in the strategy for online communication (Pérez-Curiel and Clavijo-Ferreira, 2017), causes a loss of control over the strategic decisions of fashion brands due to their independence in developing actions (Díaz, 2017). In order to describe to what extent, the influencer enhances the brand identity and the change in strategy trend in the sector, a triple-focus comparative content analysis methodology is designed (Silverman, 2016; Krippendorff, 2004). It analyzes the Instagram accounts of three international renowned luxury firms such as Gucci, Loewe and Margiela (total posts n1 = 3756 and specific posts n2 = 240) and develops a panel of experts (n3=6) aimed at specialized professionals and academics. The results indicate how the values ​​and corporate image of the brands are affected by the ego-personal discourse of these influence profiles.